Uzbek Minorities’ Experiences in Majority Higher Education Institutions - Abdurakhimova, Dilnoza (Nazarbayev University Graduate School of Education, 2017)
Kazakhstani higher education is quite diverse; there are representatives of 85 nations who are currently studying at higher education institutions. One of the representatives of these language minority groups are Uzbek students, who are taught in their native language in primary and secondary levels, learning majority languages as a subject at schools. However, the graduates of Uzbek medium schools have to continue their post-secondary education in the majority language medium HEIs, because there are no Uzbek medium programs in Kazakhstani HEIs. As a result, students who used to learn the content in Uzbek at secondary level, switch to Kazakh or Russian, which are the mediums of instruction in post-secondary level. The purpose of this study was to explore Uzbek language minority students’ experiences in majority universities. The study sought to answer the following research question: “What are the Uzbek speaking minority students’ experiences of social and academic integration in Kazakh and Russian medium programs in Kazakhstani HEIs?” The study used the qualitative phenomenological approach and the data was collected using semi-structured in-depth interviews. Seven students from Kazakh and Russian medium programs participated in the study. The study revealed that students’ social integration was relatively easier than academic integration. The challenges faced during the integration period were mostly language-oriented. Students’ language of instruction choice, either Kazakh or Russian, affected their preparation and integration. Moreover, the study pinpointed the importance of social support from teachers and administrative staff, which positively affected to students’ persistence and motivation to study. The study findings suggest that university administrations should increase the level of social and academic support and raise teachers’ awareness of approaching minority students. Also, school-counselors are recommended to guide applicants when choosing a language of the test and language of instruction in HEIs. Студенты высших учебных заведений Казахстана - представители 85 этнических и языковых групп. Одним из представителей этих групп являются представители узбекского этноса, которые обучаются на родном языке в начальной и средней школе, и изучают казахский и русский языки в качестве школьного предмета. Тем не менее, выпускники средних узбекских школ продолжают свое высшее образование на казахском и русском языках, так как Казахстанские ВУЗы не предоставляют программы с узбекским языком обучения. В результате, учащиеся, которые раньше обучались на узбекском языке, переходят на казахский или русский язык. Целью этого исследования было изучение опыта интеграции студентов из узбекских школ в ВУЗах Казахстана. Исследование отвечает на следующий исследовательский вопрос: «Каков опыт социальной и академической интеграции узбекских студентов в ВУЗах казахским и русским языками обучения?» В исследовании использовался качественный феноменологический метод, и сбор данных был осуществлен с помошью использования углубленных интервью. Семь студентов из казахских и русских программ приняли участие в исследовании. Исследование показало, что социальная интеграция студентов проходила относительно легче чем академическая интеграция. Проблемы, с которыми столкнулись студенты в период интеграции, касались в основном умения использования русского и казахского языков. Выбор языка тестирования и обучения повлиял на их подготовку к поступлению в университеты и интеграцию в университетскую среду. Кроме того, исследование выявило важность социальной поддержки со стороны учителей и администрации университета в настойчивости и мотивации студентов к учебе. Результаты исследования предполагают, что администрации университетов следует повысить уровень социальной и академической поддержки и повысить осведомленность учителей в отношении учащихся из числа языковых меньшинств. Кроме того, школьным консультантам рекомендуется предоставлять помощь и поддержку абитуриентам при выборе языка тестирования и далее языка обучения в ВУЗе.
Keywords: Uzbek minorities; higher education institutions; academic integration; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education